La violencia intrafamiliar y sus efectos en el aprendizaje en los estudiantes del tercer año de Educación General Básica. - Basantes Yugcha, Martha Cecilia (2020)
This investigation is focused on the problem of intra-family violence and its effects on the learning of the students of the Third year of Basic Education since this generates degradation in the relationships of the affective character of the family circle and consequently affects the cognitive aspect of the person. As an alternative solution to the problem is to develop a workshop, which includes sessions for both parents and students, in order to counteract the negative effects that generate this serious social problem. For this purpose, a methodology with a qualitative approach is assumed that allows describing the research problem, so that a generalization, diagnosis, theoretical references, and the proposal are established. The information has been collected to assess the current state of the problem with the use of a checklist, an interview guide, the drawing test and free story about the family, instruments applied directly to children. Whose results showed problems in their emotional state, a replica of the aggressiveness with their partners, among others? What led to the elaboration of the Workshops "Educating with love for a better future", which intends the intervention from the educational perspective to improve the conditions of children victims of violence and improve learning in each one of them. The proposal has been validated through the socialization workshop and the criteria of the user and specialists, demonstrating its feasibility.